The Change Has Come: How Transformational Leadership Makes Change Transition Successful in Islamic Banks? - Irma Suryani; Halimatussakdiah Halimatussakdiah; Amri Amri; Muharam Alfaridzi; Riska Chayyara; Nidia Sofa; Khatijatusshalihah Khatijatusshalihah (Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: A major syariah regulation in Aceh province, Indonesia, has forced conventional banks to terminate their operation in the region, and following that Islamic Banks particularly in Aceh become popular and grow significantly. As a result Bank’s operational management has changed in Aceh province. Background Problems: As anticipated, uncertainty, confusion and insecurity impacted employee performance Novelty: Transformational leadership has long been associated with change process, therefore this research tried to validate the notion with the case of Islamic Banks in Indonesia particularly in Aceh Province which has never been studied before Research Methods: This research was conducted using quantitative approach, data were collected using online questionnaires from 135 active employees in Islamic Syariah Banks and hypothesis were then tested using SEM. Finding/Results:The results show that transformational leadership significantly affects job performance during the change process at Islamic Banks in Aceh Province and self-efficacy mediates the relationship Conclusion: The study confirms that transformational leadership does affect job performance during the change process.